2022
DOI: 10.3390/cancers14081955
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Kv1.3 Channels as Target for Treatment of Multiple Myeloma

Abstract: Despite several new developments in the treatment of multiple myeloma, all available therapies are only palliative without curative potential and all patients ultimately relapse. Thus, novel therapeutic options are urgently required to prolong survival of or to even cure myeloma. Here, we show that multiple myeloma cells express the potassium channel Kv1.3 in their mitochondria. The mitochondrial Kv1.3 inhibitors PAPTP and PCARBTP are efficient against two tested human multiple myeloma cell lines (L-363 and RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The former is based on peptide DA7R, expected to target the NRP-1/VEGFR2 receptor complex in PDAC cells, as it does in other systems. As payload, i.e., chemotherapeutic active principle, we used PAPTP, a mitochondriotropic drug under development in our group [ 44 , 45 , 46 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The former is based on peptide DA7R, expected to target the NRP-1/VEGFR2 receptor complex in PDAC cells, as it does in other systems. As payload, i.e., chemotherapeutic active principle, we used PAPTP, a mitochondriotropic drug under development in our group [ 44 , 45 , 46 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that the Kv1.3 inhibitor tetrahydropyran inhibited PC cell proliferation and induced apoptosis ( 58 ). In vitro experiments revealed that the mitochondrial Kv1.3 inhibitors PAPTP and PCARBTP were able to promote apoptosis in multiple myeloma cell lines L-363 and RPMI-8226 ( 67 ). Mitochondrial targeting inhibitors have been found to alter mitochondrial function by inhibiting Kv1.3 leading to reactive oxygen species mediated apoptosis of cancer cells in vivo in vitro and in vivo experiments in melanoma and pancreatic ductal adenocarcinoma (PDAC) ( 68 ).…”
Section: Role Of Potassium Channel In Diagnosis and Treatment Of Tumormentioning
confidence: 99%
“…K V 1.3 is also recognized as a therapeutic target to modulate the function of autoreactive B cells in granulomatosis with polyangiitis [ 32 ], disease-associated microglia in Alzheimer’s disease, Parkinson’s disease and ischemic stroke [ 37–45 ], macrophages [ 46 ] and neutrophils [ 22 ] in autoimmune and neuroinflammatory diseases [ 23 ]. In addition, mitochondrial K V 1.3 is recognized as a target for the treatment of diverse tumors [ 47 , 48 ]. Since K V 1.3-knockout mice and rats do not exhibit a deleterious phenotype, selective pharmacological targeting of K V 1.3 should be safe [ 27 , 49–51 ].…”
Section: K V 13 As a Therapeutic Target For Autoim...mentioning
confidence: 99%